Robust control of a spatially distributed commercial fishery - William A. Brock; Anastasios Xepapadeas; Athanasios N. Yannacopoulos (Fondazione Eni Enrico Mattei (FEEM), 2013)
We consider a robust control model for a spatially distributed commercial fishery under uncertainty, and in particular a tracking problem, i.e. the problem of robust stabilization of a chosen deterministic benchmark state in the presence of model uncertainty. The problem is expressed in the form of a stochastic linear quadratic robust optimal control problem, which is solved analytically. We focus on the emergence of breakdown from the robust stabilization policy, called hot spots, and comment upon their significance concerning the spatiotemporal behaviour of the system.
Keywords: D81; R12; Q22; C6; 330; spatiotemporal dynamics; model uncertainty; robust control; fishery